Cytoarchitectural and Axonal Maturation in Human Auditory Cortex - Moore, Jean K. (Springer-Verlag, 2001)
This study followed the maturation of human auditory cortex from the beginning of the second trimester of gestation to young adulthood. Histological and immunohistochemical techniques were used to trace the development of a laminar cytoarchitecture and an adult pattern of axonal neurofilament expression. From the 16th fetal week to the 4th postnatal month, the cortex progresses from a marginal layer and an undifferentiated cortical plate to incipient lamination. Between the 22nd fetal week and the 4th postnatal month, a two-tiered band of neurofilament-immunoreactive axons develops in layer I, but subsequent to the 4th month, the number of immunopositive axons in this layer is greatly reduced. Between the middle of the first year of life and age 3 years, the laminar pattern of cytoarchitecture becomes fully mature and a network of immunostained axons develops in layers VI, V, IV, and IIIc. This axonal plexus in the deep cortical layers continues to increase in density until age 5. Beginning at 5 years of age, a network of neurofilament-positive axons develops in the superficial layers IIIb, IIIa, and II, and by 11-12 years of age, overall axonal density is equivalent to that seen in young adulthood. This extended time span of axonal maturation has implications for the emergence of auditory cortical function.